Legacies of Dachau: The Uses and Abuses of a Concentration Camp, 1933–2001 - Miller, Paul B. (Holocaust and genocide studies, 2003)
Legacies of Dachau: The Uses and Abuses of a Concentration Camp, 1933–2001 HaroldMarcuse CambridgeCambridge University Press 2001xxii + 590$35.00 , 1McDaniel College